Combined systems based on OSOFC/HSOFC: Comparative analysis and multi‐objective optimization of power and emission. (9th November 2020) - Mojaver, Parisa; Khalilarya, Shahram; Chitsaz, Ata
Summary: An integrated system, including a biomass gasifier, a solid oxide fuel cell, heat pipes, and an organic Rankine cycle, was modeled and validated. The system performance was assessed in two different cases based on: (a) oxygen‐ion conducting electrolyte and (b) proton‐conducting electrolyte solid oxide fuel cells. At low current densities, the system based on proton‐conducting electrolyte cell presented larger values of power. In contrast, the system based on oxygen‐ion conducting electrolyte cell had a better performance from power viewpoint at high current densities. This phenomenon was similar for energy and exergy efficiencies and emission. The comparative analysis revealed that the system based on oxygen‐ion conducting electrolyte cell had higher power output than the system based on proton‐conducting electrolyte cell (204.2 kW against 178.7 kW) at their optimum conditions, while the system based on proton‐conducting electrolyte cell presented lower emission (996.5 kg/MW h against 1560.7 kg/MW h). The TOPSIS method was utilized to solve the multi‐criteria decision‐making problem. The results indicated that the system based on proton‐conducting electrolyte cell had a better performance than the system based on oxygen‐ion conducting electrolyte cell. Abstract : In this study, a new integrated system, including biomass gasification, a SOFC, heat pipes, and an ORC, is proposed. A comprehensive comparison analysis is performed on the performances of the systems based on OSOFC and HSOFC. The effects of parameters are studied on voltage losses, Nernst and cell voltages, powers, efficiencies, and emission. The multi‐objective optimization is carried out using response surface methodology, and central composite design is utilized.